2015
DOI: 10.1016/j.jlp.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Flame acceleration in tube explosions with up to three flat-bar obstacles with variable obstacle separation distance

Abstract: The effect of obstacle separation distance on the severity of gas explosions has received little methodical study. It was the aim of this work to investigate the influence of obstacle spacing of up to three flat-bar obstacles. The tests were performed using methane-air (10% by vol.), in an elongated vented cylindrical vessel 162 mm internal diameter with an overall length-todiameter, L/D, of 27.7. The obstacles had either 2 or 4 flat-bars and presenting 20% blockage ratio to the flow path. The different number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Based on the above theory fundamentals including the flame acceleration and flame-shock interactions, a number of experimental studies [12,13,[28][29][30] have demonstrated the influence of obstacle spacing or scale on the flame propagation process. The work by Ciccarelli et al [31] demonstrated that the detonation initiation due to shock reflection is roughly the same for the different blockage ratio (BR) reflector perforated plates tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above theory fundamentals including the flame acceleration and flame-shock interactions, a number of experimental studies [12,13,[28][29][30] have demonstrated the influence of obstacle spacing or scale on the flame propagation process. The work by Ciccarelli et al [31] demonstrated that the detonation initiation due to shock reflection is roughly the same for the different blockage ratio (BR) reflector perforated plates tested.…”
Section: Introductionmentioning
confidence: 99%
“…In other work by Abdulmajid [28], the effects of obstacle scale with the same BR on the flame speed and overpressure were investigated. The obstacle with two flat bars obtained maximum overpressure compared with that with four flat bars.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when the explosion spreads throughout the pipeline, the propagation of shock waves is restricted by the sealing of the pipeline outlet. The reflection and superposition of shock wave rapidly occurred, causing a further increase in explosion pressure …”
Section: Resultsmentioning
confidence: 99%
“…Gubba et al [19] found that the flame propagation could be influenced by the number of obstacles and its blocking rate and low pressure areas could appear [12] around the next plates, whereas its blocking rate decreased during the experiment of combining the block shape with plates. In addition, Na'inna et al [20] suggested that it can cause higher pressure for appropriate blocking rate and separation distance of obstacles. After experimentation, Li et al [21] suggested these obstacles could have a great influence on the explosion overpressure and the flame propagation based on the different shapes of trapezoid, circle, square and rectangle.…”
Section: Introductionmentioning
confidence: 99%